Characterization and understanding of the tilt-dependence of core-loss spectra for hexagonal boron nitride. (November 2021) - Lahkar, Simanta; Wang, Xiaodong; Hemker, Kevin; Reddy, Kolan Madhav
Abstract: Despite great interest in the thermo-mechanical, optical, and electronic features of layered materials, the complete nature of anisotropy and its effect on their spectroscopic properties remains poorly understood due to the difficulty in characterizing the chemical bonding in different crystal orientations. Here, we use electron energy loss spectroscopy (EELS) to evaluate the tilt-dependent bonding characterization of hexagonal boron nitride (hBN), a promising layered van der Waals material, by tilting the specimen and studying the changing core-loss spectra. Our experimentally calculated values match well with the theoretically obtained curve of tilt versus relative peak intensities of the core-loss EELS spectra, which illustrates the scope for precise quantitative analysis of layered materials using EELS. Graphical abstract: Image, graphical abstract